Comparative Cost Analysis of Robotic-Assisted and Jig-Based Manual Primary Total Knee Arthroplasty - Cotter, Eric J.; Wang, Jesse; Illgen, Richard L. (The Journal of Knee Surgery, 2020)
Excellent durability with traditional jig-based manual total knee arthroplasty (mTKA) has been noted, but substantial rates of dissatisfaction remain. Robotic-assisted TKA (raTKA) was introduced to improve clinical outcomes, but associated costs have not been well studied. The purpose of our study is to compare 90-day episode-of-care (EOC) costs for mTKA and raTKA. A retrospective review of an institutional database from 4/2015 to 9/2017 identified consecutive mTKAs and raTKAs using a single implant system performed by one surgeon. The raTKA platform became available at our institution in October 2016. Prior to this date, all TKAs were performed with mTKA technique. After this date, all TKAs were performed using robotic-assistance without exception. Sequential cases were included for both mTKA and raTKA with no patients excluded. Clinical and financial data were obtained from medical and billing records. Ninety-day EOC costs were compared. Statistical analysis was performed by departmental statistician. One hundred and thirty nine mTKAs and 147 raTKAs were identified. No significant differences in patient characteristics were noted. Total intraoperative costs were higher ($10,295.17 vs. 9,998.78, respectively, p < 0.001) and inpatient costs were lower ($3,893.90 vs. 5,587.40, respectively, p < 0.001) comparing raTKA and mTKA. Length of stay (LOS) was reduced 25% (1.2 vs. 1.6 days, respectively, p < 0.0001) and prescribed opioids were reduced 57% (984.2 versus 2240.4 morphine milligram equivalents, respectively, p < 0.0001) comparing raTKA with mTKA. Ninety-day EOC costs were $2,090.70 lower for raTKA compared with mTKA ($15,629.94 vs. 17,720.64, respectively; p < 0.001). The higher intraoperative costs associated with raTKA were offset by greater savings in postoperative costs for the 90-day EOC compared with mTKA. Higher intraoperative costs were driven by the cost of the robot, maintenance fees, and robot-specific disposables. Cost savings with raTKA were primarily driven by reduced instrument pan reprocessing fees, shorter LOS, and reduced prescribed opioids compared with mTKA technique. raTKA demonstrated improved value compared with mTKA based on significantly lower average 90-day EOC costs and superior quality exemplified by reduced LOS, less postoperative opioid requirements, and reduced postdischarge resource utilization.
Keywords: robotic-assisted; total knee arthroplasty; manual; cost analysis